A business model for spa tourism enterprises: Transformation in a period of sustainable change and humanitarian crisis - Adam R. Szromek; Grzegorz Polok (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The global events of the third decade of the 21st century prove that the specter of humanitarian problems caused by health and military crises is real, and even very probable. Contemporary tourist entities, however, are not doomed only to a destructive reaction, but can also assume a significant social role for humanitarian aid. The aim of this article is to assess the changes taking place in the business models of spa services companies in the context of crisis situations caused by organizational changes and the COVID-19 pandemic. The research was conducted in 2018 and 2020, based on in-depth interviews as part of the generic contingency principle (GCP) methodology. In the course of the research, it was found that business models are not a frequently used management tool in spa enterprises. Based on the findings, a business model for spa businesses was created, followed by a more sustainable version, that can be shared in the form of open innovation. Due to the outbreak of the COVID-19 pandemic during the project, further research was done on spa enterprises regarding the use of the spa infrastructure for supporting the health system during epidemic threats.
Keywords: 650; business models; COVID-19 pandemic; open innovation; open innovation with digital transformation; sustainability; tourism enterprise